Effects of Salicylic Acid to Control Bacterial Leaf Blight Disease (Xanthomonas oryzae pv. oryzae) on Three Varieties of Rice - Siti Mai Saroh; Rachmi Masnilah (Jember University Press, 2022)
ABSTRACTBacterial leaf blight is a disease in rice plants caused by Xanthomonas oryzae pv. oryzae. The use of resistant varieties is an effective, economic and easy way to do it, but it is limited by time and place so that it needs to be induced by the addition of salicylic acid. Salicylic acid is one of the compounds that can activate enzymes that play a role in plant resistance to pathogen infection. The purpose of this study was to determine the effect of the addition of salicylic acid to rice varieties to induce its resistance to bacterial leaf blight. The research was arranged in a factorial completely randomized design (CRD) consisting of 2 factors. The first factor used was mekongga rice varieties (V1); Ciherang (V2); and IPB 3S (V3), while the second factor is the concentration of salicylic acid consisting of 0 mM (K0); 7.5 mM (K1); 10 mM (K2); and 12.5 mM (K3) with each treatment repeated 3 times, and in each study unit there were 5 plants. Results showed that the addition of salicylic acid and the use of three varieties of rice can suppress the severity of the disease HDB, its resistance status increases when compared to control and increases the content of the phenol. The best treatment of 10 mM salicylic acid concentrations with Mekongga varieties (K2V2) can suppress the severity of the HDB disease by 18.47% by showing a moderately susceptible endurance status as well as the content of the phenol increased.Keywords : Salicylic Acid, Varieties of Rice, Xanthomonas oryzae pv. oryzae